The Financial Feasibility of Launching a New Product at PT. Refractorindo Graha Dinamika - Muhammad Anandito Attaya; Isrochmani Murtaqi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study investigates the financial feasibility of launching a new product—plastic refractories—at PT. Refractorindo Graha Dinamika. The company aims to diversify its offerings while maintaining competitiveness in Indonesia's growing refractory market. The study employs a structured methodology that begins with a comprehensive business environment analysis using PESTLE and Porter’s Five Forces frameworks, then calculates the company’s Weighted Average Cost of Capital (WACC), and constructing a detailed five-year cash flow projection. Capital budgeting metrics—Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), Payback Period (PP), and Discounted Payback Period (DPP)—are applied to evaluate the financial feasibility of investing in three locally sourced manufacturing machines essential for producing plastic refractories. The results indicate that the new product is financially feasible, with a positive NPV, an IRR exceeding the WACC, and acceptable payback periods. Sensitivity analysis using Monte Carlo simulation further assesses the impact of uncertainties in sales volume on financial outcomes. The study offers insights for PT. Refractorindo Graha Dinamika’s management regarding the decision whether to accept or reject the acquisition of new capital investments.